A Root-Preferential DFR-Like Gene Encoding Dihydrokaempferol Reductase Involved in Anthocyanin Biosynthesis of Purple-Fleshed Sweet Potato - Liu, Xiaoqiang; Xiang, Min; Fan, Yufang; Yang, Chunxian; Zeng, Lingjiang; Zhang, Qitang; Chen, Min; Liao, Zhihua (Frontiers in Plant Science, 2017)
Purple-fleshed sweet potato is good for health due to rich anthocyanins in tubers. Although the anthocyanin biosynthetic pathway is well understood in up-ground organs of plants, the knowledge on anthocyanin biosynthesis in underground tubers is limited. In the present study, we isolated and functionally characterized a root-preferential gene encoding dihydrokaempferol reductase (IbDHKR) from purple-fleshed sweet potato. IbDHKR showed highly similarity with the reported dihydroflavonol reductases in other plant species at the sequence levels and the NADPH-binding motif and the substrate-binding domain were also found in IbDHKR. The tissue profile showed that IbDHKR was expressed in all the tested organs, but with much higher level in tuber roots. The expression level of IbDHKR was consistent with the anthocyanin content in sweet potato organs, suggesting that tuber roots were the main organs to synthesize anthocyanins. The recombinant 44 kD IbDHKR was purified and fed by three different dihydroflavonol substrates including dihydrokaempferol (DHK), dihydroquerctin (DHQ) and dihydromyrecetin (DHM). The substrate feeding assay indicated that only DHK could be accepted as substrate by IbDHKR, which was reduced to leucopelargonidin confirmed by LC-MS. Finally, IbDHKR was overexpressed in transgenic tobacco. The IbDHKR-overexpression tobacco corolla was more highly pigmented and contained higher level of anthocyanins than the wild-type tobacco corolla. In summary, IbDHKR was a root-preferential gene involved in anthocyanin biosynthesis and its encoding protein, specifically catalyzing DHK reduction to yield leucopelargonidin, was a candidate gene for engineering anthocyanin biosynthetic pathway.